Sons de Macabéa : possíveis notas de desejo entre a psicanálise e A hora da estrela - Neves, Nayara Lima (2017)
The present work focuses on the hope of offering an encounter between psychoanalysis and literature, by studying Clarice Lispector's work The Hour of the Star. We propose to recognize the novel‘s heroine, considering that her construction, as well as the psychoanalytic construction of the concept of desire, is made from what is rest and from what is lack. Our reading is attentive to the possible relation between both constructions, for while psychoanalysis considers desire as a residue from the lack that inaugurates it, we read in The Hour of the Star a character that, instead of lack, becomes a residue. Our conclusion seeks to point to a consideration of desire in the work The Hour of the Star, through the character that, according to its narrator, nobody saw.